Oscillatory characteristics of the visual mismatch negativity: what evoked potentials aren't telling us - Stothart, George; Kazanina, Nina (Frontiers in Human Neuroscience, 2013)
The visual mismatch negativity (vMMN) response is typically examined by subtracting the average response to a deviant stimulus from the response to the standard. This approach, however, can omit a critical element of the neural response, i.e. the non-phase-locked (‘induced’) oscillatory activity. Recent investigations of the oscillatory characteristics of the auditory mismatch negativity (aMMN) identified a crucial role for theta phase locking and power. Oscillatory characteristics of the vMMN from 39 healthy young adults were investigated in order to establish whether theta phase locking plays a similar role in the vMMN response. We explored changes in phase locking, overall post stimulus spectral power as well as non-phase-locked spectral power compared to baseline (-300-0ms). These were calculated in the frequency range of 4-50Hz and analysed using a non-parametric cluster based analysis. vMMN was found intermittently in a broad time interval 133-584ms post-stimulus and was associated with an early increase in theta phase locking (75-175ms post stimulus) that was not accompanied by an increase in theta power. Theta phase locking in the absence of an increase in theta power has been associated with the distribution and flow of information between spatially disparate neural locations. Additionally, in the 450-600 ms post-stimulus interval, deviant stimuli yielded a stronger decrease in non-phase-locked alpha power than standard stimuli, potentially reflecting a shift in attentional resources following the detection of change. The examination of oscillatory activity is crucial to the comprehensive analysis of a neural response to a stimulus, and when combined with evoked potentials (EPs) provide a more complete picture of neurocognitive processing.